How effects of local labor demand shocks vary with local labor market conditions - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2014)
This paper estimates how effects of shocks to local labor demand on local labor market outcomes vary with initial local economic conditions. The data are on U.S. metro areas from 1979 to 2011. The paper finds that demand shocks to local job growth have greater effects in reducing local unemployment rates if the local economy is initially depressed than if the local economy is booming. Demand shocks have greater effects on local wage rates if the local unemployment rate is initially low, but lesser effects if local job growth is initially high. These different effects of local demand shocks imply that social benefits of adding jobs are two to three times greater per job in more depressed local labor markets, compared to more booming local labor markets.
Keywords: R23; H43; J64; 330; Local labor markets; labor demand; social benefits of job creation